Bet Mishpachah : the gay & lesbian synagogue of Washington DC. (Washington : Bet Mishpachah, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : PO Box 1410, Washington DC 20013
Engels
Periodiek